2018
DOI: 10.24106/kefdergi.389940
|View full text |Cite
|
Sign up to set email alerts
|

Turizm Eğitimi Alan Öğrencilerin Elektronik Öğrenmeye Hazır Bulunuşluklarını Belirlemeye Yönelik Bir Çalışma

Abstract: Yapılan bu araştırmanın temel amacı önlisans düzeyinde turizm eğitimi alan öğrencilerin elektronik öğrenmeye (e-öğrenmeye) hazır bulunuşluk düzeylerini tespit etmektir. Bununla birlikte öğrencilerin e-öğrenmeye hazır bulunuşluk düzeyleri ile cinsiyet ve eğitim gördükleri bölüm değişkenleri arasında anlamlı bir farklılık olup olmadığı ise ikincil amaç olarak belirlenmiştir. Bu amacın gerçekleştirilebilmesi için oluşturulan anket, bir kamu üniversitesindeki "Otel, Lokanta ve İkram Hizmetleri ile Seyahat, Turizm … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
2
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 15 publications
3
2
0
1
Order By: Relevance
“…Another result of the present study was that, likewise, male candidate teachers' average scores were higher (Table 3). The results which turned out to be in favour of the male students in terms of e-learning readiness showed in line with the results of other studies (Haznedar, 2012;Sakal, 2017;Olcay, Döş, Sürme, & Düzgün, 2018;Yılmaz et al, 2019;İbili, 2020). On the other hand, some other studies reported no significant difference in students' e-learning readiness in terms of gender.…”
Section: Gender and Pre-service Teachers' E-learning Readinesssupporting
confidence: 90%
“…Another result of the present study was that, likewise, male candidate teachers' average scores were higher (Table 3). The results which turned out to be in favour of the male students in terms of e-learning readiness showed in line with the results of other studies (Haznedar, 2012;Sakal, 2017;Olcay, Döş, Sürme, & Düzgün, 2018;Yılmaz et al, 2019;İbili, 2020). On the other hand, some other studies reported no significant difference in students' e-learning readiness in terms of gender.…”
Section: Gender and Pre-service Teachers' E-learning Readinesssupporting
confidence: 90%
“…Another finding of this study is that male students are readier than female students. This finding is in line with the findings of online education readiness studies in the literature conducted with students in a Faculty of Medicine (Coskun et al, 2018), Tourism-related department students with no prior online education experience (Olcay, Dos, Surme, & Duzgun, 2018), and an entire sample of university students (Yilmaz et al, 2019). In contrast, there are many studies in the literature revealing that gender has no effect on online education readiness (Adnan & Boz-Yaman, 2017;Hung et al, 2010;Pala, 2018).…”
Section: Discussionsupporting
confidence: 83%
“…The results showed that there was no significant difference between the genders in the online learning scale in general, consistent with the results reported by Cakir and Horzum (2015), Adnan and Boz Yaman (2017), Kuleli (2018) and Demir Ozturk and Eren (2021). On the other hand, Olcay et al (2018) and Akbal (2021) found that the gender variable led to differences in readiness for online learning, with the readiness of males being higher than that of females. It was found that the online learning readiness of the participating pre-service social studies teachers did not show a statistically significant difference by the grade variable.…”
Section: Conclusion and Discussionmentioning
confidence: 99%